2011
DOI: 10.1039/c1jm12023a
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically structured biphenylene-bridged periodic mesoporous organosilica

Abstract: Novel composites of highly ordered and stable biphenyl-bridged periodic mesoporous organosilica (PMO) materials confined within the pores of anodic alumina membranes (AAM) were successfully synthesized by evaporation-induced self-assembly (EISA). 4,4 0 -Bis(triethoxysilyl)biphenyl (BTEBP) was used as a precursor in combination with the ionic surfactant cetyltrimethylammonium bromide (CTAB) or triblock-copolymer F127 as structure-directing agents. The resulting mesophases were characterized by small angle X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The SAXS pattern recorded with the calcined sample shows the typical peaks assigned to a body centered cubic Im 3m phase (Fig. 4A), similar to recent observations with other cubic phases in AAM hosts, 36,39 indicating that a new 3a-OPV-PMO with a cubic structure was formed. The formation of the cubic mesostructure was also conrmed by the TEM micrographs.…”
Section: F108-cubic 3a-opv-pmosupporting
confidence: 87%
See 1 more Smart Citation
“…The SAXS pattern recorded with the calcined sample shows the typical peaks assigned to a body centered cubic Im 3m phase (Fig. 4A), similar to recent observations with other cubic phases in AAM hosts, 36,39 indicating that a new 3a-OPV-PMO with a cubic structure was formed. The formation of the cubic mesostructure was also conrmed by the TEM micrographs.…”
Section: F108-cubic 3a-opv-pmosupporting
confidence: 87%
“…[28][29][30][31][32][33][34] Given the favorable interaction of silica species with AAM channel walls found in inorganic silica/AAM systems, we reasoned that combining PMO systems with porous AAM hosts might lead to a different phase behavior and phase stability, thus improving the quality of PMO materials and meanwhile opening the way to design novel hierarchical nanosystems. Based on our previous work on PMO/AAM composite systems, 35,36 the present study focuses on the synthesis of the reported charge-conducting PMO within the connement of AAM channels to achieve a new hierarchical PMO/AAM nanosystem that might move us closer to the application of PMO systems in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems include disulfide‐ and tetrasulfide‐doped PMO NPs (for glutathione‐mediated biodegradation in cells), and degradable oxamide‐ or lysine‐doped PMO NPs. Fourth, solid nonporous BS NPs can also be constructed from bridged multi‐organoalkoxysilanes (Figure D) . The absence of specific interactions between micelles and bridged organoalkoxysilanes produces dense NPs with high organic content in the composite matrix …”
Section: Two‐photon‐sensitive Organosilica Nanomaterialsmentioning
confidence: 99%
“…Over the past sixteen years, PMOs with different bridging groups, such as methylene [5][6][7], ethylene [1,2,8,9], ethenylene [2,3,6,10,11], phenylene [6,[12][13][14], biphenylene [15,16], thiophene [12,17] and so on, have been synthesized. Different structures, such as 2-dimensional (2-D) hexagonal [1,18], 3-dimensional hexagonal (P6 3 /mmc symmetry) 3 [1], cubic Pm3n [19], body-centered cubic (Im3m symmetry) [20], face-centered cubic (Fm3m) [21,22] and gyroidal cubic Ia3d structure [23], have been reported, although most of these structures were obtained for ethylene-bridged PMOs, with a much more limited set of structures demonstrated for other PMO compositions.…”
Section: Introductionmentioning
confidence: 99%